COMPUTER-AIDED DESIGN OF DRAWING MODES OF CORED WIRE IN A METAL SHEATH - GRIBKOV, E. (My University, 2018)
Determination of the minimum number of passes while ensuring continuity of the shell and the required density of the powder core of cored wire in a metal sheath.
Keywords: drawing; flux-cored wire; shell; finite element model